Comparative evaluation of shear bond strength of two adhesive materials on demineralized dentin treated with silver diamine fluoride: An in-vitro study - J Baby John; Pradeep D Gainneos; Basil M Mathew; C Bharath; Vinola Duraisamy (Wolters Kluwer Medknow Publications, 2021)
Context: Early childhood caries (ECC) is one of the most common diseases in the children of developing countries, affecting their oral health-related quality of life. From an economic perspective, silver diamine fluoride (SDF) can limit the progression of active carious lesions. Aims: To estimate and compare the loss of shear bond strength among two adhesive materials on SDF-treated demineralized primary teeth dentin. Settings and Design: Laboratory setting and in-vitro study design. Methods and Material: For the in-vitro study, 40 primary teeth indicated for extraction were selected. The demineralization solution was 5% nitric acid. The samples were divided into four groups, Group 1 - GIC Type IX, Group 2 - Self-etch (SE) adhesive + G-Aenial Universal Flo, Group 3 - SDF + GIC Type IX, and Group 4 - SDF + SE adhesive + G-Aenial Universal Flo. Statistical Analysis Used: Descriptive analysis and analysis of variance with Tukey's Post hoc test. Results: The shear bond strength of GC G-Aenial Universal Flo (18.8165 ± 13.0448 MPa) found to be superior to GIC (5.7845 ± 1.8968 MPa). However, bond strength was significantly reduced with GC G-Aenial Universal Flo (34.0441 ± 14.1949/18.8165 ± 13.0448 MPa) compared to GIC (7.7956 ± 2.2804/5.7845 ± 1.8968 MPa) following the application of SDF. Conclusions: It was concluded that SE adhesive + GC G-Aenial Universal Flo is the material with better shear bond strength compared to GIC Type IX with and without SDF. Considering the severity and prevalence of ECC, socioeconomic strata of Indian population, the choice of material for masking the discoloration, and prevention of disease, GIC can be suggested as an alternative over GC G-Aenial Universal Flo.